Profile of Wisdom and Knowledge Character on EFL Students - Fajriansyah, Syukron; Saraswati, Niken (Inspiring: English Education Journal, 2023)
In the character of the virtues of wisdom and knowledge contained in the five which include knowledge and wisdom, namely creativity, curiosity, love of strength, love of learning and perspective. The objective of this study is to provide a description of the strength of the character of the virtue of wisdom and knowledge of students who are also prospective English teachers. This study uses a survey method involving 91 respondents of prospective English teachers at one of university in Bandung, Indonesia. The data was gathered through the utilization of the Values in Action Inventory of Strengths (VIA-IS) instrument which was then analyzed using the Rasch Model. The results of the study indicate that the activity of reading scientific books to fill spare time is a character that is difficult for students to do. Meanwhile, the character will continue to find out about the information that is of interest, which is a character that is easy to implement. There are about 50.5% of respondents who tend to have a strong character in wisdom and knowledge, about 36.2% tend to be simple and 13.1% tend to be weak. Therefore, it is necessary to improve the process of strengthening the character of the virtue of wisdom and knowledge for prospective English teachers.